Clinico-Pathological Study of Tubal Ectopic Gestation and Evaluation of Associated Risk Factors in A Tertiary Care Centre - Bembde, Archana S; Bindu, Suparna M; Bhale, Chandrashekar P (Annals of Pathology and Laboratory Medicine, 2019)
Background: Ectopic gestation is an obstetric emergency with high morbidity and mortality. Most common site for ectopic pregnancy is fallopian tube. Predisposing risk factors include pelvic inflammatory disease (PID) that is acute and chronic salpingitis, previous abortion, Salphingitis Isthmica Nodosa (SIN); and treatment for infertility. This study was done to identify the common risk factors. Method: This was a retrospective study carried out for the period of 6 years (January 2013 - December 2018) in M.G.M. Medical college, Aurangabad. 110 cases of tubal ectopic gestations were studied. Results: Out of 110 ectopic gestations, commonest age of presentation was 25-35years (90.9%), and were multiparous (85.3%). Right sided tube was mostly affected (70.2%), with the risk factors of PID (32%) and previous abortion (30%). Most of the patients presented with pain in abdomen (40.90%) and amenorrhea (31.81%). Predominant histopathological findings were chronic salphingitis with follicular salphingitis (40.90%), acute salphingitis (27.27%) and SIN (22.7%). Conclusion: Pelvic inflammatory disease, Salphingitis Isthmica Nodosa, acute and chronic salphingitis are predisposing factors for tubal ectopic gestation. Early diagnosis, identification of risk factors and timely intervention will reduce the incidence of ectopic pregnancy and also will help in reducing morbidity and mortality associated with it.